2018
DOI: 10.1021/acs.energyfuels.7b03212
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Nucleation of Methyl Stearate as a Function of Crystallization Environment

Abstract: Crystallization studies of methyl stearate from supersaturated dodecane, kerosene, and toluene solutions reveal strong evidence that solvent choice influences solubility and nucleation behavior. Solute solubility is less than ideal with toluene, kerosene, and dodecane, respectively, exhibiting the closest behavior to ideality, the latter consistent with the highest solvation. Polythermal crystallization studies using the Kashchiev–Borissova–Hammond–Roberts (KBHR) model [J. Phys. Chem. B20101145441; J. Cryst. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…17 Given the lack of studies on the crystallization of saturated methyl esters, it is the aim of this study to deliver fundamental information on the morphology and crystal growth kinetics of methyl stearate as a function of solution environment. These findings are complemented and cross-correlated in section 3.3 with unpublished results, 29 where a fundamental analysis of methyl stearate nucleation was carried out.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…17 Given the lack of studies on the crystallization of saturated methyl esters, it is the aim of this study to deliver fundamental information on the morphology and crystal growth kinetics of methyl stearate as a function of solution environment. These findings are complemented and cross-correlated in section 3.3 with unpublished results, 29 where a fundamental analysis of methyl stearate nucleation was carried out.…”
Section: Introductionmentioning
confidence: 64%
“…Table presents an overview of results together with those obtained from the assessment of nucleation in the same solutions’ systems …”
Section: Resultsmentioning
confidence: 99%
“…In the current work, the PTFE-coated stirrer bar was cylindrical and had a length of 7 mm and a diameter of 2 mm. This equipment is designed for and has been used extensively for induction time, metastable zone width (through measurement of the onset of nucleation), and solubility (through measurement of the clear point) measurements in the literature. ,, …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Recently, the group of Davey has shown that shear has an effect on primary nucleation which limits the ability of some commonly used prediction methods to estimate primary nucleation rates in industrial crystallizers. Moreover, indirect measurements and mathematical models relating nucleation rate with induction times or metastable zone widths have also been developed by the group of Nyvlt, Kubota, and Kashchiev (KBHR model) under several theoretical assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this approach, it can be assessed whether the dissolution is enthalpy or entropy-driven [ 29 , 30 , 31 , 32 ]. Notably, the knowledge of entropic/enthalpic contributions to the Gibbs free energy, as well as activity coefficients in saturated solutions analysis, is of a particular importance in describing the crystallization process [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%